Metabolic profile and adipokine levels in overweight and obese dogs - De Marchi, Paula Nassar [UNESP]; Araujo Machado, Luiz Henrique de [UNESP]; Holsback, Luciane; Calesso, Jessica Ragazzi; Fagnani, Rafael; Zacarias Junior, Ademir; Lahm Cardoso, Mauro Jose (Scientific Technical Research Council Turkey-tubitak, 2020)
Obesity in dogs is increasingly present in the veterinary practice. In humans, it is known that there is a significant correlation between obesity and the development of hypertension and insulin resistance (IR), a clinical picture called metabolic syndrome. In dogs, however, there are only anecdotes about the syndrome. The objectives of this study were to determine serum levels of adiponectin, leptin, triglycerides, cholesterol, insulin, glucose, homeostasis assessment of B cell function (HOMA-B), homeostasis assessment of insulin resistance (HOMA-IR), and systolic blood pressure (SBP) in dogs with different body conditions (BC) and body fat (BF) without endocrine disease. For this purpose, 76 healthy dogs were submitted to evaluation of body conditions score (BCS) and morphometry. The dogs were separated into 3 groups: optimal BC [BCS 3,4, or 5 of 9 and BF% of 13 to 27-Group 1 (G1)], overweight [BCS 6 and 7 of 9 and BF% of 14 to 38- Group 2 (G2)], obese [BCS 8 and 9 of 9 and BF% greater than or equal to 34-Group 3 (G3)]. G3 presented higher serum levels of total protein, triglycerides, glucose, insulin, and HOMA-IR. Adipokines did not correlate to any other parameter, but the occurrence of hyperinsulinemia was higher in G3. The results have shown that obese dogs presented IR and alterations in fat metabolism.
Keywords: Adipokines; systolic hypertension; obesity; insulin resistance